The impact of heating, ventilation, and air conditioning design features on the transmission of viruses, including the 2019 novel coronavirus: A systematic review of ultraviolet radiation - Thornton, Gail M.; Fleck, Brian A.; Fleck, Natalie; Kroeker, Emily; Dandnayak, Dhyey; Zhong, Lexuan; Hartling, Lisa (PLOS ONE, 2022)
Respiratory viruses are capable of transmitting via an aerosol route. Emerging evidence suggests that SARS-CoV-2 which causes COVID-19 can be spread through airborne transmission, particularly in indoor environments with poor ventilation. Heating, ventilation, and air conditioning (HVAC) systems can play a role in mitigating airborne virus transmission. Ultraviolet germicidal irradiation (UVGI), a feature that can be incorporated into HVAC systems, can be used to impede the ability of viruses to replicate and infect a host. We conducted a systematic review of the scientific literature examining the effectiveness of HVAC design features in reducing virus transmission—here we report results for ultraviolet (UV) radiation. We followed international standards for conducting systematic reviews and developed an a priori protocol. We conducted a comprehensive search to January 2021 of published and grey literature using Ovid MEDLINE, Compendex, and Web of Science Core. Two reviewers were involved in study selection, data extraction, and risk of bias assessments. We presented study characteristics and results in evidence tables, and synthesized results across studies narratively. We identified 32 relevant studies published between 1936 and 2020. Research demonstrates that: viruses and bacteriophages are inactivated by UV radiation; increasing UV dose is associated with decreasing survival fraction of viruses and bacteriophages; increasing relative humidity is associated with decreasing susceptibility to UV radiation; UV dose and corresponding survival fraction are affected by airflow pattern, air changes per hour, and UV device location; and UV radiation is associated with decreased transmission in both animal and human studies. While UV radiation has been shown to be effective in inactivating viruses and reducing disease transmission, practical implementation of UVGI in HVAC systems needs to consider airflow patterns, air changes per hour, and UV device location. The majority of the scientific literature is comprised of experimental, laboratory-based studies. Further, a variety of viruses have been examined; however, there are few studies of coronaviruses and none to date of SARS-CoV-2. Future field studies of UVGI systems could address an existing research gap and provide important information on system performance in real-world situations, particularly in the context of the current COVID-19 pandemic. This comprehensive synthesis of the scientific evidence examining the impact of UV radiation on virus transmission can be used to guide implementation of systems to mitigate airborne spread and identify priorities for future research. Trial registration PROSPERO 2020 CRD42020193968.